Four Musical Minimalists: La Monte Young, Terry Riley, Steve Reich, Philip Glass - Pottern, keith (Cambridge Cambridge University Press, 2000)
This book offers the most detailed account so far of the early works of these four minimalist composers, putting extensive discussion of the music into a biographical perspective. The true musical minimalism of the 1960s and early 1970s is placed in the wider context of their music as a whole, and considered within the cultural conditions of the period, which saw not only the rise of minimalism in the fine arts but also crucial changes in the theory and practice of musical composition in the Western cultivated tradition
Keywords: Young, La Monte -- -1935; Riley, Terry -- 1935-; Reich, Steve -- 1936-; Glass, Philip -- 1937-; 20th Century (1901-2000); Minimalist music; Music history; USA